Effect of glycemic control on periodontitis in type 2 diabetic patients with periodontal disease. Issue 3 (14th February 2013) - Katagiri, Sayaka; Nitta, Hiroshi; Nagasawa, Toshiyuki; Izumi, Yuichi; Kanazawa, Masao; Matsuo, Akira; Chiba, Hiroshige; Fukui, Michiaki; Nakamura, Naoto; Oseko, Fumishige; Kanamura, Narisato; Inagaki, Koji; et al.
Abstract Aims/Introduction Diabetes mellitus and periodontitis are closely related. A huge number of reports has addressed the effect of periodontal intervention therapy on glycemic control, but no reports have addressed the effect of glycemic intervention therapy on periodontal disease in type 2 diabetic patients. The aim of this study was to examine the effect of improved glycemic control by glycemic intervention therapy on periodontitis in type 2 diabetic patients. Materials and Methods A total of 35 patients underwent intervention therapy to improve glycemic control without periodontal treatment. Glycohemoglobin (HbA1c), high‐sensitivity C‐reactive protein (hs‐CRP), bleeding on probing (BOP), probing pocket depth (PPD) and intraoral community periodontal index (CPI) codes of the World health Organization (WHO) were examined at baseline, and 2 and 6 months after the intervention therapy to improve glycemic control. Results After the improvement of glycemic control, BOP lesions improved, but deep PPD lesions and WHO CPI codes did not improve. Subanalyses showed that effective glycemic control (average HbA1c reduction 1.8%) improved BOP lesions, but did not affect deep PPD lesions and WHO CPI codes. In addition, high BOP lesions at baseline responded more effectively to glycemic intervention. Further analysis of CPI codes in all individual periodontal sites independent of WHO CPI codes in 35 patients showed that only gingival inflammation without a deep periodontal pocket improved after glycemic intervention. Conclusions Effective glycemic control improves BOP lesions in type 2 diabetic patients with periodontitis through ameliorating inflammation at the gingival sites of periodontal tissue. This trial was registered with the University Hospital Medical Information Network (no. UMIN000007670).